2003
DOI: 10.2190/v0wq-nwgn-jb54-fat4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Image and Animation in Enhancing Pedagogical Agent Persona

Abstract: The purpose of this experimental study was to test the role of image and animation on: a) learners' perceptions of pedagogical agent persona characteristics (i.e., extent to which agent was person-like, engaging, credible, and instructor-like); b) agent value; and c) performance. The primary analysis consisted of two contrast comparisons: 1) comparing the presence/absence of agent image; and 2) comparing static versus animated agent images. In the study, 75 preservice teachers developed an instructional plan f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
108
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(124 citation statements)
references
References 24 publications
(52 reference statements)
6
108
0
Order By: Relevance
“…Research confirms that for motivational and affective outcomes in particular, the visual presence of an agent is critical; in other words, a voice alone (human or machine generated) with the same persuasive message is not sufficient. Baylor & Ryu (2003) found that providing an anthropomorphic agent (either static or animated) together with a human voice led to greater learner perceptions of agent credibility in the context of a learning environment. More recently, in a two-way betweensubjects design of agent gender (male, female) and agent presence (visible, invisible), controlling for agent attractiveness and voice (prosody, tone), it was found that college students who interacted with visible agents reported significantly greater positive motivational outcomes.…”
Section: Visual Presence Of the Agentmentioning
confidence: 98%
“…Research confirms that for motivational and affective outcomes in particular, the visual presence of an agent is critical; in other words, a voice alone (human or machine generated) with the same persuasive message is not sufficient. Baylor & Ryu (2003) found that providing an anthropomorphic agent (either static or animated) together with a human voice led to greater learner perceptions of agent credibility in the context of a learning environment. More recently, in a two-way betweensubjects design of agent gender (male, female) and agent presence (visible, invisible), controlling for agent attractiveness and voice (prosody, tone), it was found that college students who interacted with visible agents reported significantly greater positive motivational outcomes.…”
Section: Visual Presence Of the Agentmentioning
confidence: 98%
“…They consist of the aspects of the visual and auditory presence of the APA that are hypothesized to ''make the learning experience more interesting, believable, or natural'' (p. 508). Empirical studies of these properties have explored the influence of the APA's age, gender, ethnicity, politeness, responsiveness, dynamism, and visual appeal, among others (e.g., André et al 1996;Arroyo et al 2011Arroyo et al , 2009Baylor 2011;Baylor and Kim 2004;Baylor and Ryu 2003;Craig et al 2002;Domagk 2010;Kim et al 2007;Lester et al 1997;Moreno 2004;Moreno et al 2000;Plant et al 2009;Wang et al 2008;Woolf et al 2010). Given our special interest in gender and science education, we summarize below the empirical studies that have investigated gender and motivation in relation to APAs in virtual science learning environments.…”
Section: Animated Pedagogical Agents and Student Motivationmentioning
confidence: 99%
“…the positive effect that a lifelike character has on learners [8]. It is known that a virtual character with anthropomorphic looks is likely to be accepted by learners [9]. However, findings on the benefit of an agent on the learning outcome of humans have been inconclusive [1].…”
Section: A Pedagogical Agents and Their Impact On Learningmentioning
confidence: 99%